Comparative analysis of Lactobacillus spp. fermentation in five fruit drinks: impacts on lactic acid production and cell viability - Nurhazwani Sa’aid; Joo, Shun Tan; Mohd Shamzi Mohamed; Muthulakshmi, Lakshmanan (Penerbit Universiti Kebangsaan Malaysia, 2025)
Fruit drinks, which contain at least 5% fruit juice and are typically non-fermented, provide a promising base for developing non-dairy functional beverages. Fermenting these drinks with lactic acid bacteria (LAB), recognized as safe for consumption, could enhance their health benefits and functionality. This study aimed to assess the lactic acid production and cell viability of different Lactobacillus spp. during the fermentation of fruit drinks. Five Lactobacillus spp., namely Lacticaseibacillus paracasei, Lactiplantibacillus plantarum, L. acidophilus, Lacticaseibacillus rhamnosus, and LimosiLactobacillus reuteri were utilized to ferment five different fruit drinks. Results show that L. plantarum exhibited superior cell growth and viability, with lactic acid production comparable to the other Lactobacillus spp.. Moreover, different Lactobacillus strains were found to produce varying concentrations of lactic acid across different fruit juices. This study demonstrates the viability of probiotics in fruit drinks, paving the way for the development of functional beverages with potential benefits for gut health and overall well-being.